C#9 and .NET5 - modern cross-platform development : build intelligent apps, websites, and services with Blazor, ASP.NET Core, and entity framework core using visual studio code - Price, Mark J. (Birmingham, UK : PACKT Publishing Limited, 2020)
With this new edition of C# 9 and .NET 5 - Modern Cross-Platform Development, you will not only gain an understanding of object oriented programming, working with databases, multithreading, and data encryption, but also learn how to develop websites using ASP.NET Core Razor Pages, the Model-View-Controller (MVC) pattern, and Blazor for web component user interfaces.
Hello, C#! Welcome, .NET -- Speaking C# -- Controlling Flow and Converting Types -- Writing, Debugging, and Testing Functions -- Building Your Own Types with Object-Oriented Programming -- Implementing Interfaces and Inheriting Classes -- Understanding and Packaging .NET Types -- Working with Common .NET Types -- Working with Files, Streams, and Serialization(N.B. Please use the Look Inside option to see further chapters).
Keywords: INTERNET PROGRAMMING; MICROSOFT VISUAL STUDIO